The patient patient: The importance of knowing your navigator - Sarah Wheeler; Julie Gilbert; Melissa Kaan; Eric Klonikowski; Claire Holloway (The Beryl Institute, 2015)
In Ontario, Diagnostic Assessment Programs (DAPs) have been implemented to improve the quality of care patients receive during the diagnostic phase of the cancer journey. Patient navigators play a critical role in this model by coordinating care and providing information and support to patients and their families. The objectives of this study were 1) to determine whether patient navigation in DAPs is associated with a better patient experience and 2) to examine whether patient navigation in DAPs modifies the effect of wait times and patient volumes on patient experience. Data reflecting patients' experience within the DAP were collected via survey and an average experience score was calculated for each region. To ascertain the relationship between patient experience, wait times and volumes, correlation coefficients were computed between regional patient experience scores and total regional patient volumes and between regional patient experience score and regional diagnostic wait times. To understand the impact of navigators on the patient experience, the sample was subdivided according to whether or not the respondent reported knowing their navigator. Patients who knew their navigator rated their experience significantly better than those who did not. For those who did not know their navigator, there was an inverse and significant correlation between patient experience scores and wait times; patients in regions with long waits had poorer experience scores overall. Patients who knew their navigator reported consistently good experience regardless of their diagnostic wait. The navigator appears to mitigate the negative impact of longer wait times on experience.